Portal and systemic haemodynamic response to acute and chronic administration of low and high dose isosorbide-5-mononitrate in patients with cirrhosis. Issue 1 (January 1995) - Jones, A L; Bangash, I H; Walker, J; Simpson, K J; Finlayson, N D; Hayes, P C
Abstract : Oral isosorbide-5-mononitrate (Is-5-Mn) was given in doses of 10 and 40 mg acutely and chronically (twice daily for four weeks), allowing a nitrate free interval to 25 patients with cirrhosis. Both 10 mg and 40 mg Is-5-Mn reduced the hepatic venous pressure gradient acutely and chronically, without evidence of tolerance. This was achieved by a reduction in the wedged hepatic venous pressure. The effect on mean azygos blood flow was variable with no significant mean change seen acutely or after chronic use with either dose. The variability was dependent not on the dose used but on the initial azygos flow; the flow in patients with initially low values increased and those with high azygos flows decreased after nitrate challenge. The development of the porto-collateral flow seems an important parameter in predicting haemodynamic response to Is-5-Mn.